Moderators of psychological and psychoeducational interventions for the prevention of anxiety: A systematic review. - Moreno-Peral, Patricia; Bellón-Saameño, Juan Ángel; Motrico, Emma; Campos-Paíno, Henar; Martín-Gómez, Carmen; Ebert, David D.; Buntrock, Claudia; Roca, Miquel; Conejo-Cerón, Sonia (Elsevier Science, 2020)
The aim of this study was to assess the available evidence on potential moderators of psychological and psychoeducational interventions for the prevention of anxiety. A systematic review using PubMed, PsycINFO, Web of Science, Embase, OpenGrey, and CENTRAL was performed up to October 2019. Two independent researchers assessed the fulfillment of eligibility criteria, extracted the data and performed a quality assessment of the included studies. Outcomes were moderators of the reduction of anxious symptoms or the incidence of anxiety disorders. Fourteen studies reporting results on moderator analyses performed in 13 randomized controlled trials were included. Twenty-seven potential moderators were organized into six categories: sociodemographic, clinical characteristics, cognitive variables, life events, interpersonal functioning and intervention characteristics. The most frequently examined variables were gender, age and baseline anxiety. We found insufficient evidence for all moderator categories studied. In children and adolescents, we found some studies with significant results for the low family support variable and higher levels of anxiety symptoms at baseline, which were both associated with higher effectiveness. Limited conclusions can be drawn about for whom and under what conditions interventions work in the prevention of anxiety. A strong need to improve the methodological quality and the number of moderator studies was identified.
https://openpolicyfinder.jisc.ac.uk/id/publication/13774
Keywords: Trastornos de ansiedad - Prevención; Revisiones sistemáticas (Medicina); Anxiety; Moderator; Prevention; Systematic review